Transforming the legal profession: an interview study of change managers in law. (September 2022) - Rogers, Justine; Bell, Felicity
Abstract: A lively debate progresses about change to the professions, including law, especially change in the form of managerialism. 'Managerialism' covers the methods and beliefs of managers within organisations, used to actively influence, evaluate, and 'market' professional work. But what about when that managerialism is change itself? How do we understand managerialism-as-change? This paper reports on an interview study with change managers, or 'transformation leaders' in the legal profession. Transformation leaders offer rich insights into the dynamics of professional change because they are incontrovertibly change agents. They are also themselves a form of managerial change as a new cadre of managers within the professions; managers with 'hybrid' identities whose legitimacy in professional settings is not assured. The findings presented include: the change leaders' identities; the types of change being introduced; the constraints on and affordances for change in legal practices; and how change leaders secure, and sometimes struggle to secure, the authority needed to implement change. The concluding discussion highlights the study's contributions to our understanding of professional change and managerialism in the legal context – both what changes are being pursued and how they are materialising through certain 'managerial' goals, strategies, and the interactions of those with mixed identities and status.